2022
DOI: 10.1002/jmv.27708
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events and breakthrough infections associated with COVID‐19 vaccination in the Indian population

Abstract: Vaccines against COVID‐19 provide immunity to deter severe morbidities associated with the infection. However, it does not prevent infection altogether in all exposed individuals. Furthermore, emerging variants of SARS‐CoV‐2 impose a threat concerning the competency of the vaccines in combating the infection. This study aims to determine the variability in adverse events and the extent of breakthrough infections in the Indian population. A retrospective study was conducted using a pre‐validated questionnaire e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…more exposed to infected individuals, there was not much difference in the prevalence.Arora et al, in her study also reported prevalence of breakthrough infection as 7.91% 17. Furthermore, similar to our study, the prevalence was higher among males than females.…”
supporting
confidence: 90%
“…more exposed to infected individuals, there was not much difference in the prevalence.Arora et al, in her study also reported prevalence of breakthrough infection as 7.91% 17. Furthermore, similar to our study, the prevalence was higher among males than females.…”
supporting
confidence: 90%
“…Another study reported that vaccine breakthrough infections with the Alpha and Delta variants were associated with comorbidities such as hypertension, immunosuppression, cancer, and coronary heart disease 36 . Further, the rate of severe or critical disease has been found to be higher among older individuals with comorbidities in previous studies alluding to the importance of underlying patient health and well‐being when concerned with COVID‐19 infection 37 . In a recently published study, the role of gender was stressed as a predictor for breakthrough infection 37 and there were several plausible explanation describing gender‐related difference in angiotensin‐converting‐enzyme‐2 expression, 38,39 estrogen, X‐chromosome, 40,41 and behavioral patterns in precautionary measures for COVID‐19 prevention 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“… 36 Further, the rate of severe or critical disease has been found to be higher among older individuals with comorbidities in previous studies alluding to the importance of underlying patient health and well‐being when concerned with COVID‐19 infection. 37 In a recently published study, the role of gender was stressed as a predictor for breakthrough infection 37 and there were several plausible explanation describing gender‐related difference in angiotensin‐converting‐enzyme‐2 expression, 38 , 39 estrogen, X‐chromosome, 40 , 41 and behavioral patterns in precautionary measures for COVID‐19 prevention. 42 , 43 As the virus continues to mutate, it is important to monitor, understand and further analyze the respective clinical outcomes of both vaccinated and unvaccinated groups for future variants to come.…”
Section: Discussionmentioning
confidence: 99%
“…The same observations were made on a smaller cohort of people with SM by Achiron et al ( 10 ). In several other studies, based on the general population, also younger patients reported any adverse events more often ( 11 , 12 ). Therefore, the shift toward younger patients may not be related to the coexistence of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 75%